Biocompatibility Assessment of Chlorhexidine Gluconate Versus a Natural Mouthwash Containing Olea Europaea and Opuntia Ficus-Indica in Zebrafish Embryos - Ünal, İsmail; Emekli-Alturfan, Ebru; Cansız, Derya; Yalcinkaya, Sebnem Ercalik; Beler, Merih; Eğilmezer, Gizem; Karagöz, Atakan (My University, 2025)
Various chemical solutions are available for oral hygiene and care, but these chemical solutions also cause various side effects in living systems. Therefore, the trend towards the production of highly biocompatible, natural-based oral care products has increased. This study aimed to compare the biocompatibility profiles of a conventional chlorhexidine gluconate-based mouthwash and a natural formulation containing Olea europaea leaf and Opuntia ficus-indica extracts using the zebrafish embryo model. Zebrafish embryos were exposed to two concentrations (100 ppm and 1000 ppm) of each mouthwash for 72 hours post-fertilization. Developmental properties such as mortality, hatching rate, pericardial edema, and body length were evaluated. Biochemical analyses included oxidative stress parameters and acetylcholinesterase (AChE) activity. Chlorhexidine exposure resulted in increased embryonic mortality, pericardial edema, and reduced body length. Biochemically, chlorhexidine increased lipid peroxidation and glutathione S-transferase (GST) activity while decreasing superoxide dismutase (SOD) and AChE activities. In contrast, embryos exposed to the natural formulation showed no significant developmental abnormalities and exhibited increased SOD and AChE activities without changes in lipid peroxidation. These findings provide evidence regarding the differential biocompatibility of synthetic and plant-based mouthwashes in early developmental models.
Keywords: Tıbbi Araştırmalar Deneysel; Kadın Hastalıkları ve Doğum